Fatal Cocaine Overdose due to Body Packers Syndrome a Case Report - Özer, Erdal; Şam, Bülent; Özdeş, Taşkın; Dokgöz, Halis (The Bulletin of Legal Medicine, 2005)
“Body packers” or “mules” are individuals who swallow or insert into a body cavity, containers or packages filled with illegal drugs for the purpose of smuggling past customs. A case of acute intoxication of cocaine is reported, of which two packages found in the stomach of a 24-year old black male at during autopsy and external examination was unremarkable. The internal examinations, showed edema and generalized congestion of the organs. This case report is about the death of a body packer due to cocaine intoxication following the rupture of a packet of cocaine. This case is represented in order to draw attention to body packing for suspected death cases.Key words: Cocaine, body packers syndrome, suspected death, autopsy, forensic medicine.
Keywords: cocaine; body packers syndrome; suspected death; autopsy; forensic medicine